Environmental and diagnostic study of some parasites in Barbus Xanthopterus fish of Al-Diwaniyah River - Abtisam Jasim Abbas (Al-Qadisiyah Journal of Pure Science, 2022)
The current study was concerned with investigating parasitic infections in Barbus Xanthopterus fish in Al-Diwaniyah River, for the period (July 2020-December 2020). (218) fish were collected from three different locations along the Al-Diwaniyah River. The results of the laboratory examination indicated that the fish were infected with the parasite Chilodonella Cyprinid and Eimiria sinenis. The current study recorded changes in the physical and chemical properties of Al-Diwaniyah River water, as the water temperature values, measured turbidity values, pH, electrical conductivity, hardness and TDS recorded a clear variation during the months of the study. The results of the statistical analysis indicated that there were significant differences between these variables at a level of probability (P≤0.05).